Sa'diddin Hamavi's Views on Sufi Morality and Their Specific Features - Rajabov Alisher Shavkatovich (International Journal on Integrated Education, 2026)
The article provides a comprehensive comparative analysis of the Sufi ethical system of Sa‘d al-Din al-Hammu’i within the framework of classical mystical traditions and the school of Ibn al-‘Arabi. Sufi ethics is examined not merely as a set of social norms, but as an essential dimension of human ontology, representing the soul’s return to its divine origin through the process of assimilation to the Divine Names (takhalluq bi-asma’ Allah). The study highlights how al-Hammu’i links the purification of the soul (nafs) to cosmic and metaphysical stations, comparing his approaches with Abu Hamid al-Ghazali’s psychological treatments of spiritual vices and virtues. A distinct feature of al-Hammu’i’s ethical framework is its unique integration with the science of letters (‘ilm al-huruf). While traditional Sufism articulates spiritual stations through psychological concepts, al-Hammu’i interprets the letter Alif as the supreme metaphysical symbol of moral steadfastness and rectitude (istiqamah). Furthermore, the paper investigates the correlation between outer observance of Sharia regulations and inner moral transformation, criticizing antinomian trends (ibahiyyah). It demonstrates how al-Hammu’i harmonizes profound concepts of trust in God (tawakkul), contentment (rida), and spiritual modesty (haya’) with a practical social ethos based on the principle of solitude within society (khalwat dar anjuman). The research concludes that al-Hammu’i’s ethical philosophy successfully synthesizes theoretical metaphysics with actionable spiritual practice, offering a holistic path toward the realization of the Perfect Man (al-Insan al-Kamil).